Ação das enzimas extracelulares na dinâmica da decomposição de macrófitas aquáticas - Sciessere, Luciana (2011)
Given the importance of mineralization processes to the knowledge of biogeochemical cycles in aquatic environments and aiming to detail these processes through enzymatic activities of microorganisms which act on aquatic macrophytes detritus, this study had as main goals to determine the dynamics of five enzymes activities which act on degradation of lignocellulosic wastes (endoglucanase (EC 3.2.1.4 and EC 3.2.1.91), β- xylanase (EC 3.2.1.8), β-1,4-glucosidase (EC 3.2.1.21) peroxidase (EC 1.11.1.7) and polyphenol oxidase (EC 1.10.3.2)) and the annual succession and efficiency of these enzymes during aquatic macrophytes decomposition, according to intrinsic (fiber content and chemical quality) and extrinsicconditions (temperature, pH, condition of oxygenation and proximity of sediment) in two aquatic systems. The experiments were conducted in the ecological station of Jataí (Luiz Antonio SP). For each experiment 216 litter bags (20 × 20 cm; ф pore = 0.4 mm) were prepared with fragments of Salvinia molesta (10 g (DW)), Eichhornia azurea (15 g (DW)), Cyperus giganteus (Exp. I) and Eleocharis sp. (Exp. II) (15 g (DW)) previously dried. The litter bags were incubated in 3 different sites in two depths: surface (≈ 0.2 m) and sediment-water interface (≈ 3.0 m) at Lagoa do Óleo (oxbow lagoon) in January 2008 and Represa do Beija-Flor (reservoir) in January 2009. Each sampling day (1, 3, 5, 30, 60, 90, 120, 150, 200, 250, 300 and 350) three litter bags of each depth were collected and taken to the laboratory for remaining particulate matter analysis. Taking into account the similarity observed between the systems, it was considered that those detritus were decomposed into acid environment with low nutrient availability (at least part of the year) and, mostly, aerobic (anaerobic periods could have occurred in s-w interface). The chemical quality, characterized by C:N ratio, exercised greatest influence on POMR mass loss and decay coefficients. Enzyme activity on the studied detritus was initiated at the same time of leaching process, intensively. After this period, a decrease in this activity was observed, occurring intermediate peaks. Until the 350th day of decomposition there was a predominance of hydrolytic enzymes activity in relation to oxidative enzymes. There was a direct relationship between mass loss and enzyme activity, related mainly to xylanase activity.